The crystal structure of [1-(4-(trifluoromethyl)phenyl)-3,4-dihydroquinolin-2(1H)-one], C16H12F3NO - Pu Xuewei; Meng Fanjie; Zhang Shaoliang (Zeitschrift für Kristallographie - New Crystal Structures)
C16H12F3NO, orthorhombic, P212121 (no. 19), a = 6.9928(6) Å, b = 8.9764(8) Å, c = 21.216(2) Å, V = 1331.7(2) Å3, Z = 2, Rgt(F) = 0.0583, wRref(F2) = 0.1552, T = 298 K.